Analisis Kualitas Pelayanan dalam Upaya Meningkatkan Kepuasan Anggota pada Unit Koperasi Kredit - Fauziyah , Diyani; Fahreza , Mohammad (Koaliansi : Cooperative Journal, 2022)
The research object is XYZ Credit Union. The income of the XYZ Credit Union in 2019 to 2020 has decreased. This is probably caused by the lack of management service to members (customers) of XYZ Credit Union hence it is not followed by the members participation. The research method used is descriptive analysis. The purpose of this study is to analyze the extent of service quality in the XYZ Credit Union unit able to increase member satisfaction. To find out the members' satisfaction with the implementation and to know the members' expectations for the implementation. Then the results of the assessment are analyzed by the level of expectation of its implementation with a recapitulation table and with a Cartesian diagram and then reviewed again with a gap analysis.